2013
DOI: 10.1177/1039856213475684
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic monitoring for clozapine cardiac toxicity: lessons from real-world experience

Abstract: The prevalence of cardiac dysfunction in patients commencing clozapine is high, and there are challenges in adhering with the recommended protocol for monitoring. Routine echocardiography is not useful in the detection of clozapine-associated myocarditis. Although cardiomyopathy may be identified, it is rare and associated with significant cost. Recommendations for routine echocardiographic monitoring should be re-examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 17 publications
1
20
0
4
Order By: Relevance
“…An Italian study suggested that N5% decrease in left ventricular (LV) ejection fraction occurred in one third of patients initiated on clozapine at one year follow-up [20]. Although our clinical experience includes several incidences where clozapine induced cardiomyopathy was referred to cardiology in the setting of incidentally noted reduced ejection fraction during preoperative evaluation, this has only been reported in two cases [21,22].…”
Section: Disease Frequencymentioning
confidence: 91%
See 1 more Smart Citation
“…An Italian study suggested that N5% decrease in left ventricular (LV) ejection fraction occurred in one third of patients initiated on clozapine at one year follow-up [20]. Although our clinical experience includes several incidences where clozapine induced cardiomyopathy was referred to cardiology in the setting of incidentally noted reduced ejection fraction during preoperative evaluation, this has only been reported in two cases [21,22].…”
Section: Disease Frequencymentioning
confidence: 91%
“…Chest pain was only reported in 2 cases. 2 asymptomatic patients were found to have cardiomyopathy on routine echocardiographic testing [21,22].…”
Section: Presenting Symptoms and Signsmentioning
confidence: 99%
“…There is little evidence that the cardiac adverse events can be predicted, but baseline echocardiogram and troponin are advisable. Regular echocardiograms do not have a strong evidence base and it has been suggested that they be undertaken only if clinically indicated (Murch et al, 2013;Ronaldson et al, 2011). Metabolic monitoring and advice about diet and exercise are essential.…”
Section: Treatment Resistance and Clozapinementioning
confidence: 99%
“…Many patients with treatment-resistant BD may achieve remission or response with clozapine [88••]. Despite proven effectiveness in severe BD, major concerns regarding toxicity (hematological, neurological, cardiovascular and hepatic), medical comorbidities (metabolic disturbances and cardiovascular disorders), and significant side effect profile (weight gain, sedation, acute delirium, and cognitive disturbances) continue to limit clozapine prescription [89][90][91].…”
Section: Addressing Functional Impairment In Severe Bipolar Disordermentioning
confidence: 99%